Discussion on "The action of elemental sulfur plus water on 1-octene at low temperatures" by Said-Ahmad et al. (Organic Geochemistry 59, 82–86). (October 2015) - Ding, Kangle; Adam, Pierre
Abstract: A recent article (Said-Ahmad, W., Amrani, A., Aizenshtat, Z., 2013. The action of elemental sulfur plus water on 1-octene at low temperatures. Organic Geochemistry 59, 82–86) is commented on in this discussion. Radical mechanisms proposed by Said-Ahmad et al. (2013) for the formation of sulfurized and oxidized organic compounds in experiments involving elemental sulfur and 1-octene under aqueous conditions, aimed at investigating the interaction of organic matter and sulfur compounds under geological conditions, are not compatible with their experimental results and other studies. In addition, results from the experiments aimed at demonstrating the role of HO radicals in the formation of oxidized organic compounds were incorrectly interpreted by the authors. In this discussion, alternative mechanisms for the formation of the sulfurized and oxygenated products reported by Said-Ahmad et al. (2013) are proposed.